The representations of women in the Middle Kingdom tombs of officials studies in iconography - Hudáková, Lubica 1985- (Brill, 2019)
In The Representations of Women in the Middle Kingdom Tombs of Officials Lubica Hudáková offers an in-depth analysis of female iconography in the decorative programme of Middle Kingdom non-royal tombs, highlighting changes and innovations in comparison to the Old Kingdom. Previously considered too uniform, the study represents the first systematic investigation of two-dimensional images of women and reveals their variability in space and time. Hudáková examines the roles appointed to women by analyzing how they are depicted in a variety of contexts. Taking into account their postures, gestures, garments, hairstyles, size of the body, age as well as attributes and tools used by them, along with the scene orientation, she traces diachronic and diatopic developments and regional traditions in the Middle Kingdom tomb decoration.
Keywords: Grabmal; Kunst; Frau -- Motiv; Ägypten -- Altertum; Tombs / Decoration / Egypt / History; Women in art; Women / Egypt / History / To 500; Egypt / History / Middle Kingdom, ca. 2180-ca. 1551 B.C.; Hochschulschrift